Time course of changes in the biochemical composition of peripheral lymph in breast cancer - Sh. Kh. Gantsev; A. V. Sultanbayev; R. Sh. Ishmuratova; V. Yu. Frolova; Sh. R. Kzyrgalin (ABV-press, 2014)
Many studies show that there are blood composition changes in the development of malignances. Nonetheless, to study changes inchemical composition of peripheral lymph is also an urgent problem. This paper presents the results of studying the biochemical composition of peripheral lymph in 78 patients after mastectomy or breast resection in different breast stages. The study estimated the peripheral lymph concentrations of the following indicators: total protein, albumin, globulin, fibrinogen, bilirubin, cholesterol, urea, creatinine, glucose, sodi- um, potassium, alanine aminotransferase and aspartate aminotransferase, and alkaline phosphatase. The findings suggest that considerable peripheral lymph changes occur in cancer patients, which shows the need for timely diagnosis and correction.